Impacto da Língua Brasileira de Sinais (Libras) na Programação da TV aberta brasileira - Couras, Maria F. K. B.; Avente, Ciceliane; Ramchandani, Ajay; Rodrigues, Rodrigo de L.; Ferraz, Eric da S.; Oliveira, Rodrigo R. de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
The inclusion of Brazilian Sign Language (Libras) in content produced by TV stations in Brazil has always been a major challenge. Recent solutions, such as the use of Libras avatars on broadcast television, have proven to be a viable solution for both broadcasters and digital TV receiver manufacturers. The use of avatars offers several benefits for the transmission and reception of this content. On the receiver side, the solution features low memory consumption, is easily synchronized with the video, can be disabled, and is also configurable on the screen. To evaluate the use of Libras avatars on TV, a usability survey was conducted with members of the deaf community, collecting feedback on their use compared to subtitles. During the survey, groups of signed, oral, and bilingual deaf individuals were evaluated regarding education levels and comprehension of the broadcast content. The results obtained demonstrated that the understanding of the content considering the 3D Avatar exceeds by 35% the understanding of the content considering the use of subtitles.